Chapter Medici Ambitions and Fascist Policies. (Re)reading the Relations between Italy and the Levant in the 1930s through the Historiography on Fakhr al-Dīn II - Trentacoste, Davide (Connessioni. Studies in Transcultural History, 2022)
On 13 April 1635, Druze emir Fakhr al-Dīn Maʿn was executed in Constantinople, after years of ambiguous relations with the Ottoman sultan. Exactly three centuries later, a biography of the emir was published in Rome, edited by Maronite father Paolo Carali and financed by the Fascist government. The reason why Fascism was interested in his figure can be traced back to the policy implemented by Italy in the 1930s, which sought to penetrate the territories of Lebanon and Syria. However, these were regions in which Fascist Italy had no real interest or claim, and so it sought to build a tie between the Levant and Italy by rereading the historiography of the relationship between "Faccardino" and Medici Tuscany at the beginning of the seventeenth century. By comparing the policies of the Medici and Fascism, it will be possible to highlight how, through Carali's work, the latter sought to construct a history that would support its ambitions towards the eastern Mediterranean.